2000
DOI: 10.1002/1099-0720(200101/02)15:1<101::aid-acp697>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of pixelation and blurring on masking the identity of familiar faces

Abstract: Two experiments are reported that assess how well the identity of highly familiar "famous# faces can be masked from short naturalistic television clips[ Recognition of identity was made more di.cult by either pixelating "Experiment 0# or blurring "Experiment 1# the viewed face[ Participants were asked to identify faces from both moving and static clips[ Results indicated that participants were still able to recognize some of the viewed faces\ despite these image degradations[ In addition\ moving images of face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
130
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 0 publications
11
130
0
Order By: Relevance
“…Harmon and Julesz (1973) were the first to demonstrate that pixelation reduces people's ability to recognise an image. Ever since, this finding has been replicated and extended by many others (e.g., Bachmann, 1991;Costen, Parker, & Craw, 1994, 1996Lander, Bruce, & Hill, 2001;Morrone, Burr, & Ross, 1983). Bachmann (1991) for instance, found evidence for a critical amount of pixels that is sufficient for recognising a face (i.e., 18 pixels horizontally and vertically; see also Costen et al, 1994Costen et al, , 1996.…”
Section: The Efficacy Of Masking Techniquesmentioning
confidence: 62%
See 2 more Smart Citations
“…Harmon and Julesz (1973) were the first to demonstrate that pixelation reduces people's ability to recognise an image. Ever since, this finding has been replicated and extended by many others (e.g., Bachmann, 1991;Costen, Parker, & Craw, 1994, 1996Lander, Bruce, & Hill, 2001;Morrone, Burr, & Ross, 1983). Bachmann (1991) for instance, found evidence for a critical amount of pixels that is sufficient for recognising a face (i.e., 18 pixels horizontally and vertically; see also Costen et al, 1994Costen et al, , 1996.…”
Section: The Efficacy Of Masking Techniquesmentioning
confidence: 62%
“…As recently noted by Lander et al (2001), the stimuli used by Bachmann (1991) contained pictures that only showed the face area, i.e., without the hair or any other body part. Moreover, the depicted people did not have any special characteristics like beards or glasses.…”
Section: The Efficacy Of Masking Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, participants can recognize the faces of well-known politicians and celebrities more accurately from videotaped images than from static images. This finding is especially salient when the faces are presented in sub-optimal viewing formats (e.g., blurred, inverted, or pixilated displays; [60,64,66,67]). Thus it seems that motion becomes more important as a cue to identity when the viewing conditions are sub-optimal.…”
Section: Recognizing Moving Facesmentioning
confidence: 96%
“…Since this research relates to facial images subject anonymity is impossible and the usual methods utilised to reduce recognition, such as the use of eye blocks or pixilation, are inappropriate for research where recognition is paramount. Some psychology research [76,77] suggests that pixelated faces and eye blocks do not hide the identity of the subject and covering up some of the face does not allow satisfactory resemblance evaluation, as we can recognise familiar faces even from poor quality images [78] with as few as 7 x 10 pixels representing the face [79]. Consent for publication may be provided by the subject and these must follow ethical research guidelines [80].…”
Section: Ethical Issues Relating To Facial Depiction Researchmentioning
confidence: 99%